(untitled) (Journal of Medicine, 2024)
Upper gastrointestinal tract predominant Crohn’s Disease (CD) remains an uncommon clinical entity, manifesting limited or vague symptomatology, thus delaying clinical suspicion and subsequent diagnostic evaluation. For that reason, it has not been widely described and there is a lack of clear recommendations for diagnosis or management. Standard Inflammatory Bowel Disease (IBD) evaluation including serologic testing, imaging, and endoscopy may initially not be fruitful. Furthermore, endoscopic evaluation may be inconclusive even in patients with long standing-disease. We describe a 30-year-old male who suffered long with persistent iron-deficiency anemia (IDA) and occasional melaena along with predominant axial arthropathy. Extensive in-patient testing including multiple endoscopic evaluation with standard biopsy were unfruitful. Ultimately, long standing recurrent gastric and duodenal ulcer, suggestive colonoscopy finding, and positive fecal calprotectin in a patient along with spondyloarthropathy drove us toward the diagnosis of Crohn’s disease. We started steroid, PPI, sulfasalazine and the patient is on follow up. J MEDICINE 2024; 25: 83-86